The Literature Review Analysis of The Human Resources Development in The Industry Era 4.0 Towards The Era of society 5.0 - Putra, Ardiansyah; Muslim, Muh Azis (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Since the beginning of the First Industrial Revolution (Industry 1.0), humans have realized the potential of technology as a tool for sustainable progress from time to time. During the Second Industrial Revolution (Industry 2.0), manufacturers began to switch to using electricity for assembly lines and mass production, which started in the 1870s. Then, with the application of electronic and information technology (IT), the concept of automation in the manufacturing industry was introduced during the Third Industrial Revolution (Industry 3.0) in the 1970s. In the context of the Fourth Industrial Revolution (Industry 4.0), the rapid progress of digital technology has changed the industrial world significantly, giving birth to what is called Industry 4.0. At this time human nature is increasingly complex in adapting to rapid change. However, along with advances in technology, new challenges have emerged in managing human resources effectively. Along with the Industrial Revolution, a new concept emerged known as Society 5.0, which encourages the integration of technology and social life outside of society. In the Society 5.0 era, society is expected to be able to quickly adapt to technological advances while maintaining human dignity in their professional lives. Therefore, it is important to understand how human evolution can adapt to this new paradigm. This research aims to explore the development of human resources in the context of the transition from Industry 4.0 to Society 5.0. This research uses the Systematic Literature Review (SLR) research method, which explores the development of human resources in facing the era of society 5.0, which is then prepared as a basis for determining strategic management of human resources using the PRISMA pattern. The research results show that there are implications for human resource management, organizational leadership, and job development in facing the challenges of Industry 4.0 and maximizing the opportunities provided by Society 5.0.